Endovascular coiling of large mastoid emissary vein causing pulsatile tinnitus. Issue 6 (December 2020) - Abdalkader, Mohamad; Ma, Alice; Cohen, Michael; Aliphas, Avner; Sakai, Osamu; Nguyen, Thanh N
The association of large mastoid emissary veins and pulsatile tinnitus has been reported. However, therapeutic options for this condition remain limited. We report a case of endovascular coiling of a large mastoid emissary vein in a patient with disabling pulsatile tinnitus with significant improvement of symptoms. To our knowledge, endovascular coiling of large mastoid emissary vein causing pulsatile tinnitus has not been reported.